PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PADA INSTALASI FARMASI DI RUMAH SAKIT TK III 04.06.03 DR. SOETARTO YOGYAKARTA - Wahyudiyono Wahyudiyono; Sri Wahyuning; Nisa Fadila (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2022)
The goal of the study was to determine the influence of quality dimensions consisting of physical evidence variables (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5) on patient satisfaction. This study was conducted at the Pharmaceutical Installation at Tk III Hospital 04.06.03 Dr. Soetarto with a sample size of 96 respondents. Data collection is done through questionnaires that have been tested for validity and reliability tests. The data analysis technique used is multiple linear regression. Based on the results of the analysis, it can be concluded that partially, variable physical evidence (X1), reliability (X2), responsiveness (X3), assurance (X4) and empathy (X5) have a positive and significant effect on patient satisfaction. Among the five variables, the responsiveness variable (X3) is the variable that has the most dominant effect on patient satisfaction at the Pharmaceutical Installation at Tk III Hospital 04.06.03 Dr. Soetarto Yogyakarta which is indicated by a beta value of 0.350 whose value is the closest to zero. While simultaneously the five variables both from physical evidence, reliability, responsiveness, assurance, and empathy affect patient satisfaction indicated by the calculation of F observed (721.910) > F table (1,91). On the other hand, the satisfaction determination coefficient is indicated by Adjusted R Square of 0.976. This means that customer satisfaction of 97.6% is affected by physical proof variables (X1), reliability (X2), responsiveness (X3), assurance (X4), and empathy (X5). The remaining 2.4% were affected due to other variables not thoroughly observed by the researchers.